2016
DOI: 10.1111/avsc.12241
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation assessment of native tree species in Broussonetia papyrifera‐dominated degraded forest landscape in southern Ghana

Abstract: Abbreviations F = Farmland; FU = Forest understorey; LGB = Large canopy gaps dominated by Broussonetia papyrifera; LGC = Large canopy gaps dominated by Chromolaena odorata; LR = Logging road; MAP = Mansonia altissima plantation; MDT = Modified Taungya System; NDP = Nauclea diderrichii plantation; NPLD = Non-pioneer light-demander; P = Pioneer; SB = Shade-bearer; ST = Skid trail; TIP = Terminalia ivorensis plantation. Abstract Question: Does the invasive tree species Broussonetia papyrifera facilitate the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…ough a few studies have attempted to assess the effects of the species on native vegetation, there are still contentions as different scientists have reported different effects of the species on native vegetation. For instance, while Agyeman [10] reported a positive effect of the species on indigenous species regeneration, Apetorgbor and Bosu [1] reported that the species impacts negatively on the abundance of indigenous species. Consequently, there is a need for more extensive studies on the species to establish its effect on native vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…ough a few studies have attempted to assess the effects of the species on native vegetation, there are still contentions as different scientists have reported different effects of the species on native vegetation. For instance, while Agyeman [10] reported a positive effect of the species on indigenous species regeneration, Apetorgbor and Bosu [1] reported that the species impacts negatively on the abundance of indigenous species. Consequently, there is a need for more extensive studies on the species to establish its effect on native vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the juvenile abundance of certain native species is not affected by invasion is not clearly understood but could partly be linked to species functional traits such as the seedlings of the unaffected species being shade tolerant and are therefore not affected by canopy closure by B. papyrifera (V. K. Agyeman et al, 2010;Kiama & Kiyiapi, 2001). It has also been suggested that B. papyrifera may have facilitative effects by fostering the establishment of seedlings and saplings of some native species (V. Agyeman et al, 2016;Yalley et al, 2020) but this remains a subject for further research.…”
Section: Effect Of B Papyrifera Invasion On Abundance Of Selected Native Timber Speciesmentioning
confidence: 99%
“…Consequently, there are still contentions as different scientists have reported inconsistent effects of the species on native vegetation. For instance, while Agyeman et al (2016) reported a positive effect of B. papyrifera on indigenous species regeneration in Ghana, Apetorgbor and Bosu (2011) reported that the species reduces the abundance of native species. Besides, locally, there is still scanty information about the effects of B. papyrifera on the recruitment of indigenous species.…”
Section: Introductionmentioning
confidence: 99%
“…They can act as facilitators in species with different shade tolerances and growth forms (Ledo 2015). Agyeman et al (2016) found that the richness and abundance of timber species seedlings and saplings are mainly due to the presence of facilitating pioneer tree species.…”
Section: Introductionmentioning
confidence: 99%
“…Ripley's K-function allows the analysis of spatial distribution patterns at several spatial scales and the detection mixed processes (association and repulsion at some scales) (Fonton et al 2012;Fajardo et al 2006). Since reforestation with native species may strongly contribute to the regeneration or restoration of degraded forests (Omelko et al 2018;Agyeman et al 2016), such analyses are important in forest management since they could improve our understanding of the role of pioneer species in maintaining plant diversity. They should enable a reasoned choice about distances between conspecific or heterospecific trees for ecological restoration of habitats and sustainable management of threatened species.…”
Section: Introductionmentioning
confidence: 99%